Optimalisasi Pemasaran Produk Olahan Makanan melalui Penerapan Strategi Digital Marketing bagi UMKM di Medan - Hendra Jonathan Sibarani; Yenni; Nora Anisa Br Sinulingga; Sari Mariahma Nova Sipayung; Sri Ramadhany; Sahara Abdy; Denni; Errie Margery; Ali Syah Putra; Debora Tambunan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The development of digital technology has significantly changed product marketing patterns, including for Micro, Small, and Medium Enterprises (MSMEs). It is known that many MSME food processing actors in Medan Marelan District have not been able to take advantage of the potential of digital marketing optimally in developing their businesses. The main problems faced include limited knowledge about digital marketing strategies, lack of ability to manage business social media, and lack of understanding of the importance of digital content-based promotion. This Community Service Activity (PKM) aims to empower food processing MSME actors in Medan Marelan through training and assistance in the implementation of digital marketing strategies to increase marketing reach and product competitiveness. The method of implementing activities includes the socialization stage, theoretical training on the basic concepts of digital marketing, direct practice of creating business accounts, creating promotional content, using marketplaces and social media, and evaluating the results of mentoring. The results of the activity showed that participants experienced an increase in knowledge and skills in the application of digital marketing. Business actors are starting to be able to create and manage business accounts independently, create attractive promotional content, and utilize various digital platforms such as Instagram, Facebook, and TikTok to expand the market.